Механізми та особливості ціноутворення на туристичному ринку - Шквиря, Наталя Олександрівна; Shkvyria, Natalia; Кукіна, Наталя Володимирівна; Kukina, Natalia (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті розглядається процес ціноутворення на туристичному ринку, його особливості та ключові фактори, що впливають на формування вартості туристичних послуг. Проведено систематизацію зовнішніх та внутрішніх факторів, що визначають механізми ціноутворення в туризмі. Проаналізовано специфічні властивості туристичного ринку, зокрема високу еластичність попиту, сезонність, часові розриви між купівлею та споживанням продукту, а також ефект взаємозамінності напрямків. Наведено приклади практичних підходів до формування цін, включно з дискримінаційним ціноутворенням, знижками за обсяг, залежністю вартості від чисельності групи, застосуванням плаваючих тарифів та впливом цифрових технологій. Визначено практичні підходи і методи встановлення кінцевої ціни з метою підвищення ефективності цінової політики туристичних підприємств та їх конкурентоспроможності. Розроблено пропозиції щодо підвищення ефективності діючої системи ціноутворення. /// EN: The article is devoted to the study of pricing mechanisms in the tourism market and the identification of key factors that influence the formation of prices for tourist services. In the modern context of increasing competition and rapid changes in market conditions, effective pricing strategies are crucial for ensuring the sustainability and profitability of tourism enterprises. The study analyzes both external and internal factors affecting pricing decisions. External factors include economic, political, social, and technological conditions, market trends, seasonality, and consumer behavior. Internal factors include enterprise costs, pricing policies, service quality, and the characteristics of the offered tourism products. Special attention is given to the specifics of pricing in tourism, including high price elasticity of demand, variability of prices depending on season, destination, and group size, the presence of substitutes, and the impact of digital technologies and online platforms on price formation. The research highlights practical approaches to determining optimal prices, such as cost-based pricing, competitive pricing, marketing-oriented pricing, value-based pricing, and rent-based approaches. The advantages and limitations of each method are discussed, emphasizing the necessity of combining different approaches to achieve a balanced and effective pricing strategy. Examples of practical applications are provided, including price discrimination for different customer segments, dynamic pricing according to demand fluctuations, and the bundling of services into tourist packages to increase perceived value. The results of the study provide recommendations for tourism enterprises on how to optimize pricing strategies, improve competitiveness, and ensure a sustainable level of profitability. The comprehensive approach proposed in the article allows for the consideration of a wide range of factors that affect pricing, making it possible to make informed decisions under conditions of uncertainty and market volatility. The study contributes to the understanding of tourism market dynamics and serves as a practical guide for managers, marketing specialists, and researchers interested in pricing policy, strategic planning, and the development of competitive advantages in the tourism sector.
Mechanisms and features of pricing in the tourism market
Keywords: ціна; ціноутворення; туристичних ринок; туристичне підприємство; фактори ціноутворення; price; pricing; tourism market; tourism enterprise; pricing factors